Churches of the Canons Regular of the Holy Sepulchre. Based on the studies on patrocinia and relics (12th to 16th c.) - Jerzy Rajman (Folia Historica Cracoviensia, 2015)
The author presents the findings of his own studies on the presence of relics and dedications in the churches of Canons Regular of the Holy Sepulchre in medieval Polonia Minor (covering the former Krakow and Sandomierz voivideships). The article reveals important accounts in Samuel Nakielski’s chronicle. The first account relates bringing the soil from Jerusalem by Jaksa and is known in literature. The second account concerns the possession of the relics of the Holy Cross by the monastery of Canons Regular of the Holy Sepulchre, hitherto unknown in literature. The author formulates a thesis on the existence of important relics of the Passion in the Miechów monastery. Key source accounts on dedications were analysed. It was indicated that the primary dedication of the Miechów church towards the end of the 18th century was a combined invocation of the Holy Sepulchre, the Holy Spirit and Blessed Virgin Mary. The author also extensively analyses the dedication of the church in Żarnowiec, with dedications to both feasts related to the Holy Cross, to the Holy Spirit, the Holy Sepulchre and Blessed Virgin Mary. The dedications of 10 other churches administered by Canons Regular of the Holy Sepulchre are also discussed. In addition, the author presents a substantial collection of data on the dedications of surviving altars and chapels in relation to the Miechów church and St Jadwiga’s Church in Stradom. In conjunction with the information on numerous relics of saints, the findings should become a departure point for further studies.